(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article analyzes the dependence on gadgets. Nomophobia in the modern world and this dependence at different age stages have been investigated. Definitely the main causes of addiction. Found that nomophobia have people of different ages, different sexes in approximately equal amounts. Various ways to get rid of human dependence on gadgets are described. It is concluded that dependence on a mobile phone is a disease of the XI century which progresses without knowing the boundaries and treatment is possible only if the person recognizes this problem, the desire to get rid of the smartphone and concrete examples of ways to get rid of nomophobia are given.